2007
DOI: 10.1590/s0101-81752007000400025
|View full text |Cite
|
Sign up to set email alerts
|

Predação de ninhos de Trachemys dorbigni (Duméril & Bibron) (Testudines, Emydidae) no extremo sul do Brasil

Abstract: Ninhos da tartaruga tigre-d'água, Trachemys dorbigni, foram monitorados durante a estação reprodutiva de 2005/2006 para avaliar as taxas de predação e a variação temporal destas; identificar as espécies predadoras, sua importância na destruição dos ninhos e determinar a influência da dispersão dos ninhos sobre a predação, no extremo sul do Brasil. Dos 58 ninhos monitorados, 98% (n = 57) foram destruídos por predadores. Eventos de predação ocorreram predominantemente nas primeiras 48 horas após a oviposição e n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
9
1
6
Order By: Relevance
“…Skunks also take advantage of some temporarily available resources, such as eggs of freshwater turtles and ground-nesting birds. We found no evidence of consumption of eggs, but they probably represent an important energy source in some regions, such as the coastal regions of southern Brazil and Uruguay, where Gonçalves et al (2007) reported the predation of 98% of turtle nests, 31% of them by Conepatus chinga. In a study of the spatial ecology of C. chinga, Kasper et al (2012b) recorded several instances of skunks preying on turtle and bird nests to eat eggs, mainly in summer.…”
Section: Discussioncontrasting
confidence: 60%
“…Skunks also take advantage of some temporarily available resources, such as eggs of freshwater turtles and ground-nesting birds. We found no evidence of consumption of eggs, but they probably represent an important energy source in some regions, such as the coastal regions of southern Brazil and Uruguay, where Gonçalves et al (2007) reported the predation of 98% of turtle nests, 31% of them by Conepatus chinga. In a study of the spatial ecology of C. chinga, Kasper et al (2012b) recorded several instances of skunks preying on turtle and bird nests to eat eggs, mainly in summer.…”
Section: Discussioncontrasting
confidence: 60%
“…Uruguai e nordeste da Argentina (VANZOLINI, 1997). No Brasil, ocorre no Rio Grande do Sul (ERNST, 1990;BAGER et al, 2007b;FAGUNDES, 2007;GONÇALVES et al, 2007;BUJES, 2008) Hábitat e ecologia. Ocupa ambientes aquáticos como lagunas, rios, banhados, lagos e açudes com abundância de vegetação (BUJES, 2008), como a lagoa Mangueira e Estação Ecológica do Taim; banhados formados pelas águas do rio Santa Bárbara, em Pelotas; banhados, arroios e meandros formadores do Delta do rio Jacuí e Reserva Biológica do Lami, em Porto Alegre (C. S. Bujes, obs.…”
Section: Família Emydidaeunclassified
“…Estes ninhos apresentaram tamanho da abertura entre 42 e 49 mm, tamanho da câmara de incubação entre 85 e 100 mm e profundidade média do ninho 116,92 mm. Indivíduos constroem ninhos de maneira solitária (GONÇALVES et al, 2007;FAGUNDES, 2007;BUJES, 2008), porém, dependendo da disponibilidade de locais para a nidificação, pode ocorrer destruição dos mesmos em virtude da atividade de outras fêmeas sobre ninhos já finalizados, o que foi observado, por duas ocasiões, em um sítio de desova reduzido na Ilha da Pintada, Porto Alegre (C. S. Bujes, obs. pess.).…”
Section: Família Emydidaeunclassified
See 1 more Smart Citation
“…Several authors have suggested that predation risk should change over the nesting season due to shifts in predator activity related to nest availability or to predator learning (Stancyk, 1982;Nellis & Small, 1983;Leighton, Horrocks & Kramer, 2009), but seasonal changes in predation risk have only been documented in a few studies (Fowler, 1979;Talbert et al, 1980;Engeman et al, 2003). In addition, various studies have reported more frequent nest predation near the start (Stancyk, Nellis & Small, 1983;Goncalves, Cechin & Bager, 2007;Leighton et al, 2009) or the end (Fowler, 1979;Nellis & Small, 1983) of incubation, but the relationship between daily predation risk and nest age has not been rigorously explored.…”
Section: Introductionmentioning
confidence: 99%